2007
DOI: 10.1002/cne.21573
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of GABAA receptor subunits within the substantia nigra of the human brain: An immunohistochemical study

Abstract: Gamma-aminobutyric acid(A) (GABA(A)) receptors (GABA(A)R) are inhibitory heteropentameric chloride ion channels comprising a variety of subunits and are localized at postsynaptic sites within the central nervous system. In this study we present the first detailed immunohistochemical investigation on the regional, cellular, and subcellular localisation of alpha(1), alpha(2), alpha(3), beta(2,3), and gamma(2) subunits of the GABA(A)R in the human substantia nigra (SN). The SN comprises two major regions, the SN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 91 publications
14
29
0
Order By: Relevance
“…Converging lines of evidence suggest that the activity of DA neurons in the VTA is under tonic inhibitory control by GABA-A receptors (Fritschy and Mohler, 1995;Pirker et al, 2000;Waldvogel et al, 2008). Specifically relevant to this study, systemic administration of GABA-A receptor inverse agonist, FG7142 has been shown to activate VTA neurons (Murphy et al, 1996).…”
Section: Introductionmentioning
confidence: 80%
“…Converging lines of evidence suggest that the activity of DA neurons in the VTA is under tonic inhibitory control by GABA-A receptors (Fritschy and Mohler, 1995;Pirker et al, 2000;Waldvogel et al, 2008). Specifically relevant to this study, systemic administration of GABA-A receptor inverse agonist, FG7142 has been shown to activate VTA neurons (Murphy et al, 1996).…”
Section: Introductionmentioning
confidence: 80%
“…In temporal neocortex, ␣2 expression is strongest in layers II and III (Loup et al, 2006) and in layers II, IV, and V in motor cortex (Petri et al, 2003). No ␣2 expression was detected in the substantia nigra (Waldvogel et al, 2008). In hu- 246 man hippocampus, the ␣2 subunit is very abundant throughout the hippocampal formation, the expression being strongest in dentate molecular layer (Loup et al, 1998(Loup et al, , 2000.…”
Section: B Expression Of Gaba a Receptor Subunits In The Human Brainmentioning
confidence: 99%
“…The GABA A R system is highly conserved in mammals, but some quantitative and/or qualitative differences have been found between human and rat in brain regional expression patterns of the subunits. The expression of some subunits is very restricted; e.g., the expression of ␣6 subunit is confined to cerebellar granule cells (Hadingham et al, 1996), whereas ␣1 is widely expressed in most brain regions (Houser et al, 1988;Akbarian et al, 1995;Loup et al, 2006;Waldvogel et al, 2008;Fatemi et al, 2009). Some cell types express only a small repertoire of subunit mRNAs (e.g., ␣1, ␤2, ␤3 and ␥2 in cerebellar Purkinje cells) (Wisden et al, 1992), whereas the majority of individual human dentate granule neurons express 10 or more different subunit mRNAs (Brooks-Kayal et al, 1999).…”
Section: B Expression Of Gaba a Receptor Subunits In The Human Brainmentioning
confidence: 99%
See 2 more Smart Citations